Metformin augments doxorubicin cytotoxicity in mammary carcinoma through activation of adenosine monophosphate protein kinase pathway - Nahla E El-Ashmawy; Naglaa F Khedr; Hoda A El-Bahrawy; Hend E Abo Mansour (Tumor Biology)
Since the incidence of breast cancer increases dramatically all over the world, the search for effective treatment is an urgent need. Metformin has demonstrated anti-tumorigenic effect both in vivo and in vitro in different cancer types. This work was designed to examine on molecular level the mode of action of metformin in mice bearing solid Ehrlich carcinoma and to evaluate the use of metformin in conjunction with doxorubicin as a combined therapy against solid Ehrlich carcinoma. Ehrlich ascites carcinoma cells were inoculated in 60 female mice as a model of breast cancer. The mice were divided into four equal groups: Control tumor, metformin, doxorubicin, and co-treatment. Metformin (15 mg/kg) and doxorubicin (4 mg/kg) were given intraperitoneally (i.p.) for four cycles every 5 days starting on day 12 of inoculation. The anti-tumorigenic effect of metformin was mediated by enhancement of adenosine monophosphate protein kinase activity and elevation of P53 protein as well as the suppression of nuclear factor-kappa B, DNA contents, and cyclin D1 gene expression. Metformin and doxorubicin mono-treatments exhibited opposing action regarding cyclin D1 gene expression, phosphorylated adenosine monophosphate protein kinase, and nuclear factor-kappa B levels. Co-treatment markedly decreased tumor volume, increased survival rate, and improved other parameters compared to doxorubicin group. In parallel, the histopathological findings demonstrated enhanced apoptosis and absence of necrosis in tumor tissue of co-treatment group. Metformin proved chemotherapeutic effect which could be mediated by the activation of adenosine monophosphate protein kinase and related pathways. Combining metformin and doxorubicin, which exhibited different mechanisms of action, produced greater efficacy as anticancer therapeutic regimen.